2006
DOI: 10.1152/ajpgi.00353.2005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental colitis in mice and sensitization of converging visceral and somatic afferent pathways

Abstract: Chronic pain syndromes affecting different organs often coexist. We hypothesized that sensitization of one afferent pathway may affect converging input from other areas of the body. We induced colitis in mice with 2,4,6-trinitrobenzenesulfonic acid (TNBS); control animals were treated with equal volumes of vehicle (50% ethanol) only. Visceromotor responses to graded colorectal distension, cystometrograms, and response thresholds to mechanical and thermal stimulation of both hind paws were determined on days 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 63 publications
6
84
1
3
Order By: Relevance
“…Acute bladder inflammation also reduces the efficacy of cannabinoid agonists on the uterine horn (21). In addition, others have recently reported that acute cystitis increases abdominal wall muscle activity that is evoked by distention of the untreated colon (55) and, conversely, that acute, as well as chronic, colon irritation induces bladder overactivity (41,55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute bladder inflammation also reduces the efficacy of cannabinoid agonists on the uterine horn (21). In addition, others have recently reported that acute cystitis increases abdominal wall muscle activity that is evoked by distention of the untreated colon (55) and, conversely, that acute, as well as chronic, colon irritation induces bladder overactivity (41,55).…”
Section: Discussionmentioning
confidence: 99%
“…The estrous influences on the cross-system effects observed here suggest that the effects are influenced by ovarian hormones, possibly estradiol. Although most previous studies of cross-organ influences between the colon and bladder have not investigated such influences (e.g., 41,43,54,55,57), the present results are consistent with findings showing that the severity of vaginal hyperalgesia induced by abdominal endometriosis correlates with circulating levels of estradiol (18). In that study, the hyperalgesia was greatest in proestrus (high level of estradiol and low level of progesterone) and was completely alleviated in estrus (very low estradiol and progesterone), a result similar to that observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, infection with the nematode Trichinella spiralis led to an increase in visceral sensitivity to pain for several weeks after the inflammation had subsided (1). However, the development of postinflammatory hyperalgesia after a transient inflammation in mice was not observed with TNBS, acetic acid, capsaicin, or mustard oil (20,23). It is not known yet whether DSS-induced colitis also causes postinflammatory visceral hyperalgesia.…”
mentioning
confidence: 99%
“…The most common technique used in pre-clinical study of visceral nociception is the visceromotor response to hollow organ distension, described in detail elsewhere [15].…”
Section: Glt-1 Activators Relieve Visceral Nociceptionmentioning
confidence: 99%